Assessment Of The Existing And Proposed Dike System Along The Cabulig River In Lower Jasaan, Misamis Oriental, Philippines - J. Jr. R. Vallente; N. D. Jr. Cipriano; Ma. E. V. Ponce; J. G. Gamale; K. A. B. Daroy; C. V. Cruza; A. S. I. Cabugsa (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The issue of flooding in the town of Jasaan in Misamis Oriental province poses a threat to 42% of the population. This is more worrisome during the rainy season, especially in the months of October and December were typhoons are at their strongest and passes in proximity to Mindanao island. Residents have reported significant damage to their properties due to flooding, and typhoons like Super Typhoon Odette in December 2021 have worsened the situation when it brought rain while the dike system was dilapedated. The dike systems in the area have been damaged by these natural disasters, and the lack of repair has made the situation worse. Flood hazard mitigation measures have since been implemented. With the frequent occurrence of flooding in the Cabulig River, a validated model is needed to investigate the behavior of the river during strong and significant rainfall events while taking into consideration the current state of the existing dike systems by coupling the modelling systems HEC-HMS and HEC-RAS. Data from the USGS, DOST-PAGASA, DPWH, and Landsat 8 have been used in this study. The results of the Flood Inundation Analysis showed that most of the flooded areas in Barangay Lower Jasaan and Bobontugan are urban areas which exacerbates during heavy rain events. The results of the simulations of the researchers' proposed dike structures shows that it should be extended towards the upstream direction and a minimum dike height of 2.5m is needed with no discontinuities. A 2.5m high dike on the Bobontugan side should also be placed.